2022
DOI: 10.4314/jpb.v19i3.3
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS analysis and invitro cytotoxic activity of Ocimum basilicum (Lamiaceae) volatile oil and active fraction composed majorly of estragole

Abstract: Ocimum basilicum leaves contain some bioactive compounds and this study was designed to evaluate the cytotoxic efficacy of its volatile oil and fractions. Preliminary screening of the oil obtained by hydrodistillation was carried out using bench-top assay methods employing tadpoles of Raniceps ranninus (10-40 μg/mL), nauplii of Artemia salina (10-1000 μg/mL) and radicles of Sorghum bicolor seeds (1-30 mg/mL). Application of column chromatography and preparative TLC on the oil resulted in fractions that were te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…For O. basilicum essential oil, our analysis revealed that estragole was the main component, accounting for 48.94% of the oil, followed by linalool (16.61%) and limonene (8.37%). These results are in line with previous studies [43][44][45], which also identified estragole as the main component of O. basilicum essential oil. Furthermore, the presence of linalool and limonene in significant proportions is consistent with the literature [46,47].…”
Section: Chemical Analysissupporting
confidence: 93%
“…For O. basilicum essential oil, our analysis revealed that estragole was the main component, accounting for 48.94% of the oil, followed by linalool (16.61%) and limonene (8.37%). These results are in line with previous studies [43][44][45], which also identified estragole as the main component of O. basilicum essential oil. Furthermore, the presence of linalool and limonene in significant proportions is consistent with the literature [46,47].…”
Section: Chemical Analysissupporting
confidence: 93%